Keynes, Cocoa, and Copper In Search of Commodity Currencies - Sahay, Ratna (International Monetary Fund, 2002)
This paper examines whether the real exchange rates of commodity-exporting countries and the real prices of their commodity exports move together over time. Using IMF data on the world prices of 44 commodities and national commodity export shares, we construct new monthly indices of national commodity export prices for 58 countries over 1980-2002. A long-run relationship between real exchange rates and real commodity prices is found for about two-fifths of the commodity-exporting countries. Also, the behavior of the real exchange rate of commodity currencies is found to be independent of the nominal exchange rate regime. The average half-life of adjustment of real exchange rates to commodity-price-augmented purchasing power parity is found to be about eight months, which is much shorter than Rogoff's (1996) consensus estimate of three to five years, and provides an important missing piece of the PPP puzzle